218k views
3 votes
If f(a) = x + 3, 9(2) = X – 7 and h(x) = Vă, thenf(g(h(x)) =

If f(a) = x + 3, 9(2) = X – 7 and h(x) = Vă, thenf(g(h(x)) =-example-1
User Cfprabhu
by
4.6k points

1 Answer

0 votes

Given the functions:


\begin{gathered} f(x)=x^4+3 \\ g(x)=x-7 \\ h(x)=\sqrt[]{x} \end{gathered}

We will find f(g(h(x)))

First, we will find g(h(x))

So, we will substitute with x=h(x) into the function g(x)

So,


g(h(x))=\sqrt[]{x}-7

Then, to find f(g(h(x))), we will substitute with x = g(h(x)) into the function f(x)

So, the answer will be:


f(g(h(x)))=(\sqrt[]{x}-7)^4+3

User Dejwi
by
5.0k points